Major Histocompatibility Complex I Mediates Immunological Tolerance of the Trophoblast during Pregnancy and May Mediate Rejection during Parturition - Anna Rapacz-Leonard; Małgorzata Dąbrowska; Tomasz Janowski (Hindawi Limited, 2014)
During pregnancy in larger mammals, the maternal immune system must tolerate the fetus for months while resisting external infection. This tolerance is facilitated by immunological communication between the fetus and the mother, which is mediated by Major Histocompatibility Complex I (MHC I) proteins, by leukocytes, and by the cytokines secreted by the leukocytes. Fetal-maternal immunological communication also supports pregnancy by inducing physiological changes in the mother. If the mother "misunderstands" the signal sent by the fetus during pregnancy, the fetus will be miscarried or delivered preterm. Unlike any other maternal organ, the placenta can express paternal antigens. At parturition, paternal antigens are known to be expressed in cows and may be expressed in horses, possibly so that the maternal immune system will reject the placenta and help to expel it. This review compares fetal-maternal crosstalk that is mediated by the immune system in three species with pregnancies that last for nine months or longer: humans, cattle, and horses. It raises the possibility that immunological communication early in pregnancy may prepare the mother for successful expulsion of fetal membranes at parturition.